A critical appraisal of comparative advantage theory under free market crony capitalism - Prabhakar, Akhilesh Chandra; Zainal Abidin, Irwan Shah; Saha, Asish (Business Perspectives, 2015)
This paper investigates comparative advantage theory and principle which is suggested that price of factors and commodities determined by the supply and the demand forces in free market conditions, the market forces automatically allocate resources efficiently that have the property that someone can be made better off without someone being made worse off, it means equally redistributed incomes.The paper identifies the root causes of the problems of inequality among people and between nations, and find the problem of worldwide inequality is the final outcome/product of free market and crony capitalism. The study explores theoretically, conceptually, and empirically through surveying literatures both primary and secondary sources.Finally, various policies and recommendations are highlighted.